2008
DOI: 10.1016/j.jpubeco.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency enhancing taxation in two-sided markets

Abstract: This paper examines the efficient provision of goods in two-sided markets and characterizes optimal specific and ad-valorem taxes. We show that (i) a monopoly may have too high output compared to the social optimum; (ii) output may be reduced by imposing negative value-added taxes (subsidy) or positive specific taxes.JEL Code: D4, D43, H21, H22, L13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 8 publications
4
91
0
1
Order By: Relevance
“…3 Thus, the standard argument in the literature in favor of ad valorem taxation is reproduced: for any given unit tax imposed on a monopoly, there exists an ad valorem tax that revenue-dominates the unit tax.…”
Section: Discussionmentioning
confidence: 99%
“…3 Thus, the standard argument in the literature in favor of ad valorem taxation is reproduced: for any given unit tax imposed on a monopoly, there exists an ad valorem tax that revenue-dominates the unit tax.…”
Section: Discussionmentioning
confidence: 99%
“…To incorporate this as simply as possible, we hold on to the assumption that newspaper readers are indifferent to the ad level in the newspaper (this is not a critical assumption; see Kind et al 2008). 9 However, we assume that demand for ads is increasing in newspaper circulation ( / 0).…”
Section: Price and Quantity Effects Of Value-added Taxesmentioning
confidence: 99%
“…11 What happens to the advertising level and advertising price depends on the exact shape of the demand and cost function, which we will not discuss here (see Kind et al, 2008, for an analysis). However, it can be shown that both the advertising level and newspaper sales might increase under reasonable assumptions.…”
Section: Price and Quantity Effects Of Value-added Taxesmentioning
confidence: 99%
“…Taxation in two-sided markets has also been examined (see, for example, Kind, Koethenbuerger, andSchjelderup 2008, 2010;Bourreau, Caillaud, and De Nijs, forthcoming). Once again demand complementarities alter the results from traditional one-sided markets.…”
mentioning
confidence: 99%
“…Once again demand complementarities alter the results from traditional one-sided markets. For a monopoly platform, Kind, Koethenbuerger, and Schjelderup (2008) show how an increase in ad valorem tax on one side of the market may result in overproduction (compared to the social optimum), with an increase in output on both sides of the market. For example, an increase in the ad valorem tax on side E may lead the platform to raise sales on side F. To do so, the platform would need to increase output on both sides E and F given their mutual dependence.…”
mentioning
confidence: 99%